Tinjauan Terhadap Hadiá¹¡ Tentang IhtikÄr dan Praktiknya di Indonesia - Hilyatin, Dewi Laela; Mukhtar, Naqiyah; Athoillah, Mohamad Anton (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Review of Hadiá¹¡ Regarding IhtikÄr and Its Practice in IndonesiaOne of the causes of market distortion is ihtikar, which is an act of hoarding goods needed by the community so that there is a shortage of goods in the market. So great is the impact of ihtikar, this can be seen from the many hadiths of the Prophet that discuss ihtikar. In this paper, the approach taken is a literature study approach to thematic hadith studies. Data were taken by means of documentation, and analyzed using qualitative descriptive methods. Based on the research conducted, it can be concluded that ihtikar is a prohibited and sinful act for the perpetrator; ihtikar can cause monopoly but monopoly is not always caused by ihtikar. Several cases of hoarding that occurred in Indonesia were related to the basic needs of the community. Among the items that have been stockpiled and caused problems are fuel, cooking oil, sugar, rice, onions, and several other basic necessities. Ihtikar has caused economic instability and harmed society. Because the impact caused by ihtikar is quite large. So the Indonesian government intervened to solve the problem. One of the interventions is through laws and regulations and several other policies